Mini-Review: The Administration of Apoptotic Cells for Treating Rheumatoid Arthritis: Current Knowledge and Clinical Perspectives - Toussirot, Eric; Bonnefoy, Francis; Vauchy, Charline; Perruche, Sylvain; Saas, Philippe (Frontiers in Immunology, 2021)
Rheumatoid arthritis (RA) is a chronic immune-mediated disease managed by conventional synthetic drugs, such as methotrexate (MTX), and targeted drugs including biological agents. Cell-based therapeutic approaches are currently developed in RA, mainly mesenchymal stroma cell-based approaches. Early-stage apoptotic cells possess direct and indirect anti-inflammatory properties. During the elimination of dying cells (a process called efferocytosis), specific mechanisms operate to control immune responses. There are compelling evidences in experimental models of arthritis indicating that apoptotic cell administration may benefit joint inflammation, and may even have therapeutic effects on arthritis. Additionally, it has been demonstrated that apoptotic cells could be administered with standard treatments of RA, such as MTX or TNF inhibitors (TNFi), given even a synergistic response with TNFi. Interestingly, apoptotic cell infusion has been successfully experienced to prevent acute graft-versus-host disease after hematopoietic cell transplantation in patients with hematologic malignancies, with a good safety profile. In this mini-review, the apoptotic cell-based therapy development in arthritis is discussed, as well as its transfer in the short-term to an innovative treatment for patients with RA. The use of apoptotic cell-derived factors, including secretome or phosphatidylserine-containing liposomes, in RA are also discussed.